"Romanticizing Penniless Entrepreneurs?" The Relationship between Start-Ups and Human Wellbeing across Countries - Wim A. Naudé; José Ernesto Amorós; Oscar Cristi M. (Institute for the Study of Labor (IZA), 2013)
We study the effect of entrepreneurship and its allocation between necessity and opportunity entrepreneurship on three indicators of countries' wellbeing: monetary wellbeing, non-monetary wellbeing and our own indicator of a country's ability to translate economic growth into non-monetary wellbeing. We take into consideration that there is a feedback effect from monetary and non-monetary wellbeing to entrepreneurial allocation. Using data from the Global Entrepreneurship Monitor we establish that opportunity entrepreneurship may contribute towards national wellbeing and that better wellbeing in turn may stimulate opportunity entrepreneurship. Hence, entrepreneurship may contribute towards countries' wellbeing in a broad sense, and countries with higher levels of wellbeing may contribute towards opportunity entrepreneurship.
Keywords: I31; M13; O50; 330; entrepreneurship; wellbeing; development; Global Entrepreneurship Monitor